Phosphorous Supplementation Alleviates Drought-Induced Physio-Biochemical Damages in Calligonum mongolicum - Abd Ullah; Akash Tariq; Fanjiang Zeng; Jordi Sardans; Corina Graciano; Sami Ullah; Xutian Chai; Zhihao Zhang; Maierdang Keyimu; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Josep Peñuelas (Plants, 2022)
Calligonum mongolicum is a phreatophyte playing an important role in sand dune fixation, but little is known about its responses to drought and P fertilization. In the present study, we performed a pot experiment to investigate the effects of P fertilization under drought or well-watered conditions on multiple morpho-physio-biochemical attributes of C. mongolicum seedlings. Drought stress leads to a higher production of hydrogen peroxide (H2O2) and malondialdehyde (MDA), leading to impaired growth and metabolism. However, C. mongolicum exhibited effective drought tolerance strategies, including a higher accumulation of soluble sugars, starch, soluble protein, proline, and significantly higheractivities of peroxidase (POD) and catalase (CAT) enzymes. P fertilization increased the productivity of drought-stressed seedlings by increasing their growth, assimilative shoots relative water content, photosynthetic pigments, osmolytes accumulation, mineral nutrition, N assimilation, and reduced lipid peroxidation. Our findings suggest the presence of soil high P depletion and C. mongolicum high P requirements during the initial growth stage. Thus, P can be utilized as a fertilizer to enhance the growth and productivity of Calligonum vegetation and to reduce the fragility of the hyper-arid desert of Taklamakan in the context of future climate change.